Elevated microRNA-7 inhibits proliferation and tumor angiogenesis and promotes apoptosis of gastric cancer cells via repression of Raf-1. Issue 19 (1st October 2020) - Lin, Jing; Liu, Zewa; Liao, Shasha; Li, E; Wu, Xiaohua; Zeng, Wanting
ABSTRACT: Objective: Since the essential involvement of microRNAs (miRNAs) in the development and progression of GC, the study was for the exploration of the value of microRNA-7 (miR-7) in the evaluation of neoadjuvant chemotherapy for gastric cancer (GC) and its effects on apoptosis, proliferation and angiogenesis of GC. Methods: miR-7 expression in serum of GC patients before and after neoadjuvant chemotherapy were detected to explore its role in neoadjuvant chemotherapy of GC. The GC cells were transfected with miR-7 mimics/inhibitors, or siRNA-Raf-1 to figure out their roles in proliferation, migration, invasion, cycle distribution and apoptosis. Tumor xenograft was conducted to test tumor growth. Microvessel density (MVD) in tumors was tested by immunohistochemical staining. Results: miR-7 expression in serum of GC patients was lower than that of healthy controls while it was elevated after neoadjuvant chemotherapy. Moreover, higher miR-7 expression was exhibited in chemotherapy-effective patients rather than chemotherapy-ineffective patients ( P < 0.01). miR-7 expression in serum was connected with tumor size, degree of differentiation, TNM stage and lymphatic metastasis.miR-7 was decreased and Raf-1 was elevated in GC cells (both P < 0.05). Elevated miR-7 or declined Raf-1 inhibited GC cell migration, proliferation and invasion, cell cycle entry, xenografted tumor growth and MVD and stimulated apoptosis (all P < 0.05). Down-regulated Raf-1 reversed the impacts of miR-7 knockdown on GC cells (all P < 0.05). Conclusion: Our study highlights that elevated miR-27a indicates the good efficacy of neoadjuvant chemotherapy in GC and miR-7 targets Raf-1 to suppress tumor development and angiogenesis of GC cells.